Analisis Perbandingan Campuran Batubara dengan Serbuk Kayu dalam Memanfaatkan Batubara Kalori Rendah di PT. Atoz Nusantara Mining Nagari Tambang IV Jurai Pasisir Selatan - Al Afdil Fadli; Murad Murad (Journals Mining Engineering : Bina Tambang, 2018)
Coal is a source of energy used as fuel. PT. Atoz Nusantara Mining is a coal mining company located in Nagari Tambang IV Jurai Pasisr Selatan. Currently coal mining activities are less effective because they are low in caloric value. Low calorie coal is piled up in stockpile and not sold. To be marketed, need to increase the value of calories or processing to be sold and utilized. Sawdust waste creates problems in handling and has not been optimally utilized. The waste is left to rot and be burned by sawmill or wood worker. Research with this method uses sawdust with the aim that low-calorie coal mixed with sawdust can be used. Based on the results of the study it can be concluded that the mixing of coal with sawdust can increase the calorific value of coal which in the sample 1 calorie coal 2186 cal / gr with a ratio of 25:75 to 3915 cal / gr. In the sample 2 calories of coal 4298 cal / gr with a ratio of 75:25 to 4249 cal / gr. In the sample 3 calories of coal 1757 cal / gr with a ratio of 25:75 to 3700 cal / gr. Other parameters such as water content, ash content, flying substances and sulfur content also changed, in sample 1 moisture in analysis 6.28% with a ratio of 75:25 to 4.32%; ash content 54.68% with a ratio of 25:75 to 10.66%; volatile matter 8.50% with a ratio of 75:25 to 29.28%; sulfur 0.55% with a ratio of 25:75 to 0.16%. In sample 2 moisture in analysis was 5.80% with a ratio of 75:25 to 4.46%; ash content 37.40% with a ratio of 25:75 to 11.33%; volatile matter 6.60% with a ratio of 75:25 to 26.79%; sulfur 1.17% with a ratio of 25:75 to 0.29%. In sample 3 moisture in analysis was 6.02% with a ratio of 75:25 to 4.28%; ash content 61.91% with a ratio of 25:75 to 15.65%; volatile matter 6.32% with a ratio of 75:25 to 30.48%; sulfur 1.17% with a ratio of 25:75 to 0.09%. Keywords: coal, low-calorie, sawdust, waste of sawdust, fuel